Analisis faktor-faktor yang mempengaruhi kepatuhan wajib pajak orang pribadi dengan kesadaran pajak sebagai varibael intervening pada wajib pajak orang pribadi di wilayah Jakarta Barat - Karlinah, Lady (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine and analyze the effect of knowledge and understanding of taxation, quality of tax services, tax sanctions, application of e-filing, and ability to pay taxes on individual taxpayer compliance in the West Jakarta area. This study uses primary data where data is collected using a questionnaire. This research was conducted on individual taxpayers registered in the West Jakarta area with a sample of 100 respondents. The results of the analysis show that knowledge and understanding of taxation has no effect on tax awareness. The quality of tax service services has no effect on tax awareness. Tax sanctions affect tax awareness. The application of e-filing affects tax awareness, the ability to pay taxes does not affect tax awareness, tax base affects individual taxpayer compliance, knowledge and understanding of taxation affects individual taxpayer compliance, the quality of tax service services does not affect individual taxpayer compliance . Tax sanctions affect the compliance of individual taxpayers. The implementation of e-filing has an effect on individual taxpayer compliance, the ability to pay taxes has no effect on individual taxpayer compliance. For the results of the intervening variable, if the five independent variables are used together, tax awareness will not mediate, but if partially it can be shown that the mediating variable is the independent variable of the quality of service of the tax authorities and the ability to pay taxes with the dependent variable being individual taxpayer compliance.